Attapulgite, charcoal and graphite phase carbon nitride composite photocatalytic body as well as preparation method and application of attapulgite, charcoal and graphite phase carbon nitride composite photocatalytic body
By constructing a composite photocatalyst of concave and concave rock stone/biochar/graphite phase carbon nitride, the coupling effect of biochar and g-C3N4 is used to solve the shortcomings of existing adsorbents and photocatalysts, and efficient adsorption of Cr(VI) and visible photocatalytic reduction, with good application prospects.
Patent Information
- Application Number
- CN202411921062.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-25
- Publication Date
- 2025-04-25
AI Technical Summary
The existing adsorbents have small adsorption capacity, slow adsorption rate and narrow pH range for Cr(VI) which limit their application. In addition, traditional photocatalysts have narrow spectral response range and low catalytic efficiency, making it difficult to be used in industrial use.
The blending of concave and concave rock stone, corn stalk and dicyandiamide is used to construct the concave and concave rock stone/biochar/graphite phase carbon nitride composite photocatalyst through high-temperature thermal decomposition. The coupling effect of biochar and g-C3N4 is used to broaden the photoresponse range of g-C3N4 and improve the photocatalytic activity.
It realizes efficient adsorption of Cr(VI) and catalytic reduction of visible light, solves the adsorption capacity and rate of adsorbent, and improves the catalytic efficiency of photocatalysts, with good application prospects.
Smart Images

Figure CN119869582A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of environmentally friendly composite new materials, and in particular to an attapulgite biochar graphite phase carbon nitride composite photocatalyst, and a preparation method and application thereof. Background Art
[0002] Chromium is the most commonly used heavy metal in industrial production and one of the key heavy metal pollutants. Its toxicity varies greatly depending on the valence state. Trivalent chromium has very low toxicity and is one of the essential trace elements for the human body. It plays a special role in the body's sugar metabolism and lipid metabolism. Unlike trivalent chromium, hexavalent chromium has a high biological toxicity, which is more than 300 times that of Cr(III).
[0003] In view of the serious harm of Cr(VI) pollution, my country has strict regulations on the Cr(VI) concentration limits of various water bodies and solid waste leachates. Among them, the limits of Cr(VI) in my country's "Standard for Drinking Water Hygiene" (GB5749-2006) and "Integrated Wastewater Discharge Standard" (GB8978-2002) are 0.05 and 0.5 mg / L respectively; the Cr(VI) concentration limit of solid waste leachate in the "Hazardous Waste Identification Standard Leaching Toxicity Identification" (GB50853-2007) is 5 mg / L. Gansu Province is a major chromium salt province in China. There are a large number of chromium salt factories built by mining companies in Baiyin City, Jiuquan City, and Zhangye City. The historical chromium pollution sites and chromium slag sites have caused serious harm to the production and life of local residents. Therefore, it is of great significance to effectively remove Cr(VI) in the soil. In recent years, the efficient removal of Cr(VI) has also become one of the research hotspots.
[0004] At present, the main methods for removing Cr(VI) include electrochemical catalysis, ion exchange, chemical precipitation, photocatalytic reduction, adsorption, etc. Among the many treatment methods, adsorption has the advantages of economy, environmental protection, simple process flow, stable and reliable operation, etc. It is particularly suitable for the treatment of Cr(VI) wastewater and the remediation of Cr(VI) contaminated soil. However, most of the existing adsorbents have problems such as low adsorption capacity, slow adsorption and narrow optimal pH range, which limits their application.
[0005] Therefore, researching and developing adsorbents with higher adsorption capacity, faster adsorption rate and wider pH range has become an urgent problem to be solved.
[0006] Studies have found that clay minerals have excellent adsorption capacity and environmental remediation effects on Cr (VI) due to their large specific surface area, high adsorption capacity, strong ion exchange capacity and biocompatibility. Attapulgite (ATP), also known as palygorskite, is a layered chain structured hydrated magnesium-rich aluminum silicate clay mineral. It is known as "the king of thousands of soils" due to its wide range of uses. It is mainly distributed in Gansu, Jiangsu, Anhui and other provinces in my country. Gansu has abundant prospective reserves of attapulgite, which is mainly distributed in Linze County, Zhangye City, Huining County and Jingyuan County, Baiyin City, and the attapulgite produced in Linze County, Zhangye City is mostly brick red iron-rich attapulgite. Attapulgite has excellent selective adsorption performance and a large adsorption capacity. It can be used for heavy metal wastewater treatment, remediation of heavy metal contaminated soil and adsorption treatment of other toxic substances.
[0007] Studies have shown that attapulgite has great potential in the above fields. Acid activation and thermal activation can significantly change the specific surface area of attapulgite, increase its adsorption performance and promote the cation exchange capacity of attapulgite. However, there is only a single hydroxyl functional group on the surface of attapulgite, and studies have found that attapulgite has limited coordination and complexing ability for heavy metal ions due to its structural negative charge and surface negative charge.
[0008] Biochar (BC) refers to a class of stable, highly aromatic, carbon-rich solid substances produced by high-temperature pyrolysis (<700°C) of biomass materials under anaerobic or anoxic conditions. Biochar has good adsorption capacity due to its physical and chemical properties such as developed pore structure, rich surface functional groups and a large number of surface charges. It has been widely used in the fields of water purification, heavy metal adsorption, soil improvement, etc. my country is a large agricultural country with rich reserves of crop straw resources. According to the data on the output of major crops provided in the 2018 "China Statistical Yearbook", the theoretical total output of major crop straw in 2017 was about 884 million tons, of which corn straw was about 404 million tons. Zhangye City is the largest hybrid corn seed production base in the country, accounting for more than 50% of the national corn seed production. A large amount of corn straw agricultural and forestry waste is generated in the production process of corn seeds, and biomass resources are extremely rich.
[0009] The adsorption method also has the disadvantages of large differences in the adsorption performance of the adsorbent material, unstable adsorption effect, difficulty in regeneration, and difficulty in handling the adsorbent after saturated adsorption, causing secondary pollution. Therefore, constructing a reaction system with excellent adsorption performance and good in-situ reduction ability of Cr (VI) has become an urgent problem to be solved.
[0010] In recent years, with the development of photocatalytic technology, the study of photocatalytic reduction of Cr(VI) has attracted the interest of many researchers.
[0011] However, most traditional photocatalysts have large band gaps and narrow spectral response ranges; photogenerated electron-hole pairs are easy to recombine, and the photocatalytic quantum yield is low; photocatalysts have poor selective adsorption performance and insufficient stability, and are easily deactivated, and metal catalysts cause new pollution to the environment. These have limited the industrial application of photocatalytic technology to a certain extent. Therefore, how to improve the spectral response range and catalytic efficiency of photocatalysts has become a key issue in the industrialization of photocatalytic technology.
[0012] Since Professor Wang Xingchen's research group first discovered in 2009 that g-C3N4 can be used in the field of photocatalysis, g-C3N4 has attracted widespread attention from scientific researchers due to its simple preparation, low cost, stability, semiconductivity and medium band gap width (about 2.7 eV). It fully shows that g-C3N4 is a non-toxic and relatively efficient non-metallic semiconductor material, and there are literatures showing that g-C3N4 and its composite materials have good photocatalytic reduction performance for Cr(VI). At present, the reactants commonly used to prepare g-C3N4 are cyanamide, dicyandiamide, melamine, cyanuric chloride, urea, thiourea and other cheap nitrogen-rich compounds, and the synthesis methods of g-C3N4 include thermal polymerization, high temperature and high pressure, deposition and solvent thermal methods. The main synthesis methods are solvent thermal method and thermal polycondensation method.
[0013] There are many large cyanamide plants in Jinchang City and Gulang County in the Hexi Corridor of Gansu Province. The rich resources of cyanamide and dicyandiamide can provide high-quality raw materials for the preparation of graphite phase carbon nitride. 3 N 4 There are also some limitations, such as the easy recombination of photogenerated carriers, low specific surface area and porosity, and narrow visible light response range. Summary of the invention
[0014] Purpose of the invention: To provide a better attapulgite biochar graphite phase carbon nitride composite photocatalyst and its preparation method and use. The specific purpose can be seen in the multiple substantial technical effects of the specific implementation part.
[0015] In order to achieve the above purpose, the present invention adopts the following technical solutions: The attapulgite biochar graphite phase carbon nitride composite photocatalyst is characterized in that its components are attapulgite biochar graphite phase carbon nitride.
[0016] The method for preparing a attapulgite biochar graphite phase carbon nitride composite photocatalyst is characterized in that attapulgite, corn straw and dicyandiamide are mixed, the mixture is pyrolyzed at high temperature, and a attapulgite / biochar / graphite phase carbon nitride composite photocatalytic system is constructed.
[0017] A further technical solution of the present invention is to use the organic functional groups generated in the biomass pyrolysis process to modify the surface structure of the attapulgite to prepare an attapulgite / biochar composite material with excellent adsorption performance for Cr(VI), and use it as a catalyst carrier to increase the gC by using the large specific surface area of the carrier. 3 N 4 The dispersion on the carrier surface increases the photocatalytic active sites and broadens the gC 3 N 4 The light response range is wide enough to achieve the adsorption of Cr(VI) and in situ visible light photocatalytic reduction of Cr(VI) under visible light conditions.
[0018] A further technical solution of the present invention is that a one-pot method is used to prepare the mixture during high-temperature pyrolysis; biochar and attapulgite have a higher specific surface area, which can show enhanced adsorption performance for pollutants and increase the contact between the composite material and the pollutants; in addition, the larger specific surface area of the carrier can increase gC 3 N 4 The surface dispersion of the photocatalyst can be improved to prevent its agglomeration, providing more active sites for the photocatalytic reaction; secondly, the dispersed photocatalyst can improve the separation efficiency of photogenerated carriers and increase the photocatalytic activity; the adsorption of cracked oil by attapulgite can improve the single hydroxyl functional group on its surface and increase the active sites for the adsorption reaction with Cr(VI).
[0019] A further technical solution of the present invention is that the attapulgite is purified attapulgite; its preparation method is to use attapulgite raw soil and a sodium hexametaphosphate container, stir the micro-suspension, and then use heating and ultrasonic stirring to make an ultra-dispersed attapulgite particle suspension, and then obtain purified attapulgite after standing and stratification.
[0020] A further technical solution of the present invention is that attapulgite and crushed corn straw are physically blended and pyrolyzed to prepare a attapulgite / biochar composite material. While preparing corn straw-based biochar by high-temperature pyrolysis, the attapulgite is thermally activated to increase the specific surface area of the attapulgite and adsorb cracking oil, forming a large number of organic functional groups on the surface of the attapulgite, which synergistically increase the adsorption and complexing capacity of Cr (VI) with the excellent physical and chemical properties of biochar and can repair damaged soil.
[0021] A further technical solution of the present invention is that the pyrolysis temperature of the mixture is 300-700°C.
[0022] A further technical solution of the present invention is that after the attapulgite, corn straw and dicyandiamide are blended, a uniform suspension is obtained by ultrasonic stirring, and then the attapulgite biochar graphite phase carbon nitride composite photocatalyst is obtained by suction filtration and drying.
[0023] The invention discloses a use of a attapulgite biochar graphite phase carbon nitride composite photocatalyst as a substance for adsorbing heavy metals.
[0024] The use of attapulgite biochar graphite phase carbon nitride composite photocatalyst as a substance for in-situ photocatalysis and reduction of composite materials; or the use of attapulgite biochar graphite phase carbon nitride composite photocatalyst as a substance for in-situ photocatalysis and reduction of composite materials or as a substance for adsorbing heavy metals at the same time.
[0025] The present invention adopting the above technical solution has the following beneficial effects compared with the prior art: 1) Solve the bottleneck problems of small adsorption capacity of Cr(VI), secondary pollution and unstable reduction efficiency of traditional adsorbents, and provide technical support for the high-value utilization of local advantageous resources.
[0026] 2) Through biochar and gC 3 N 4 The coupling effect is expected to broaden the gC 3 N 4 The visible light response range can be expanded to improve the separation efficiency of photogenerated carriers, solve local prominent environmental protection problems, and provide technology for the practical application of photocatalytic technology.
[0027] 3) Systematically study the adsorption mechanism during the reaction, the separation of electron-hole pairs during the photocatalytic reduction reaction, charge transfer, the interaction between the catalyst surface and Cr(VI), and other scientific issues, providing a basis for future exploration of the basic photocatalytic reduction reaction mechanism.
[0028] Preparation of ATP / BC / gC by calcination in one pot 3 N 4 Composite photocatalytic material, using attapulgite to adsorb cracked oil to improve its single hydroxyl functional group on the surface, increasing the adsorption reaction active sites with Cr(VI). 3 N 4 The binding of gC 3 N 4 Therefore, the implementation of this project has good application prospects.
[0029] 2) In combination with the regional resource advantages and environmental hydrological characteristics of Zhangye City, Gansu Province, local attapulgite, corn straw and nitrogen-rich industrial products are used to prepare Cr(VI) adsorption and removal materials in chromium-contaminated soils, which provides a feasible idea for the development and utilization of local advantageous resources and a feasible solution for the treatment of local chromium-contaminated soils. The implementation of the project has certain social value. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] In order to further illustrate the present invention, the following is further described in conjunction with the accompanying drawings: Figure 1 ATP / BC / gC 3 N 4 Schematic diagram of composite photocatalytic system adsorption and in situ visible light photocatalytic reduction of Cr(VI); Figure 2 The implementation process of this patent; Figure 3 For separation, purification and structural characterization of attapulgite; Figure 4 ATP / BC / gC 3 N 4 Preparation and structural characterization of composite photocatalytic materials; Figure 5 ATP / BC / gC 3 N 4 Test of the adsorption and photocatalytic reduction performance of composite photocatalytic materials on Cr(VI); Figure 6 ATP / BC / gC 3 N 4 Flow chart of remediation of Cr(VI) contaminated soil using composite photocatalytic materials. DETAILED DESCRIPTION
[0031] The present invention will be further explained below in conjunction with the accompanying drawings and specific embodiments. It should be understood that the following specific embodiments are only used to illustrate the present invention and are not used to limit the scope of the present invention.
[0032] It is planned to combine the local resource advantages (rich reserves of attapulgite in Linze, Zhangye, Gansu, with excellent quality; abundant agricultural and forestry wastes such as corn straw in Zhangye City; high-quality cyanamide resources in the Hexi Corridor) with the regional environmental ecological defects (a large number of chromium salt plants and chromium slag yards in Gansu Province), mix different proportions of Linze attapulgite, corn straw and dicyandiamide, pyrolyze the mixture at different temperatures, construct an attapulgite / biochar / graphite phase carbon nitride composite photocatalytic system, and prepare a composite material with excellent adsorption performance and in situ photocatalytic reduction performance for Cr(VI). The purpose is to use the organic functional groups generated in the biomass pyrolysis process to modify the surface structure of attapulgite to prepare an attapulgite / biochar composite material with excellent adsorption performance for Cr(VI), and use it as a catalyst carrier to increase the gC by utilizing the large specific surface area of the carrier. 3 N 4 The dispersion on the carrier surface increases the photocatalytic active sites and broadens the gC 3 N 4 The photoresponse range is 100%. The purpose of adsorbing Cr(VI) and in situ visible light photocatalytic reduction of Cr(VI) under visible light conditions is achieved (Figure 1).
[0033] In summary, the present invention is based on the regional advantage mineral resource attapulgite, agricultural and forestry waste corn stalks and bulk industrial product dicyandiamide, with the purpose of Cr(VI) adsorption and complexation and then in-situ visible light catalytic reduction to Cr(III), and prepares a series of attapulgite / biochar / graphite phase carbon nitride composite photocatalytic materials by one-pot calcination and studies the Cr(VI) adsorption behavior and photocatalytic reduction mechanism, in order to obtain a cheap composite material with good Cr(VI) adsorption performance and in-situ visible light catalytic reduction performance, the method is simple, green and environmentally friendly. Through the implementation of this project, the research ideas of high-value utilization of attapulgite and agricultural and forestry waste and efficient utilization of solar energy can be enriched, the application scope of attapulgite can be expanded, and scientific basis and technical support can be provided for the remediation of chromium-contaminated soil.
[0034] The present invention aims to develop cheap, green and efficient ATP / BC / gC 3 N 4For the purpose of composite photocatalytic materials, attapulgite, corn straw and dicyandiamide were used for high temperature pyrolysis, and a composite material with excellent adsorption performance and in-situ photocatalytic reduction performance for Cr(VI) was prepared by a one-pot method and its structure was characterized. The adsorption capacity of a series of composite materials for Cr(VI) was explored through adsorption tests, and 3-5 composite materials with strong adsorption capacity for Cr(VI) were screened out, and their adsorption mechanism was further explored; the in-situ photocatalytic reduction performance of the composite material was tested under visible light conditions, and its photocatalytic reduction mechanism was explored; finally, the chromium-contaminated soil of Zhangye Minle Chromium Salt Plant was used to systematically investigate the actual application performance of the composite material.
[0035] Preparation and structural characterization of composite photocatalytic materials The Linze attapulgite raw soil was purified by dispersant-assisted ultrasonic hydrothermal method, and the purified attapulgite was mixed with corn straw powder and dicyandiamide in different ratios, different pyrolysis temperatures (300-700℃), and different reaction times to prepare a series of functional materials with strong adsorption capacity for Cr(VI). The composite materials were structurally characterized by (XRD, SEM, FTIR, BET, XPS, TG-DSC and Zeta potential) to study the microscopic morphology and material structure changes of the composite materials.
[0036] The effects of factors such as the dosage of composite materials, pH value, adsorption time, initial Cr(VI) ion concentration, coexistence of competing cations, and adsorption temperature on the Cr(VI) adsorption performance of composite materials were investigated to determine the optimal adsorption conditions of the composite materials. Under the selected conditions, the adsorption and desorption regeneration capacity of the composite materials was studied. At the same time, the influence of interfering ions was investigated, and on this basis, the isothermal adsorption model, kinetic adsorption model, and thermodynamic adsorption model were used to fit the experimental data, determine the use model, and preliminarily determine and analyze the adsorption mechanism during the adsorption process.
[0037] Study on the photocatalytic reduction performance of composite photocatalytic materials for Cr(VI) The photocatalytic reduction performance of the composite material for Cr(VI) was systematically studied under visible light conditions, and the effects of catalyst dosage, solution pH value and temperature on the photocatalytic reduction activity were investigated. The electron transfer and electron-hole separation mechanism during the photocatalytic reaction were studied using ultraviolet diffuse reflectance spectroscopy (UV-vis), fluorescence spectroscopy (PL), electrochemical impedance spectroscopy, transient photocurrent action spectroscopy and cyclic voltammetry. The relationship between the carrier and gC in the high-efficiency composite photocatalytic material was clarified. 3 N 4 The interaction between them affects the photocatalytic reduction process of Cr(VI). The focus is on revealing the adsorption mechanism of Cr(VI) by the composite material and the in-situ photocatalytic reduction mechanism of Cr(VI) by the photocatalyst.
[0038] Practical performance testing of the best composite photocatalytic materials Combined with the qualified ATP / BC / gC screened in the previous step 3 N 4 Composite photocatalytic materials, select composite materials with practical application value for actual application performance evaluation, take the chromium-contaminated soil of Zhangye Minle Chromium Salt Plant, examine the actual Cr(VI) removal performance of qualified composite materials under the above conditions, and propose and verify the Cr(VI) removal plan in drinking water and contaminated soil.
[0039] ATP / BC / gC 3 N 4 Composite photocatalytic materials have the following outstanding advantages: 1. Innovatively integrate the advantageous resources of Gansu Province, combine the regional resource advantages and environmental hydrological characteristics of Zhangye City, Gansu Province, and use local attapulgite, corn stalks and nitrogen-rich industrial products as materials for the adsorption and removal of Cr(VI) in chromium-contaminated soil; According to calculations, this technology can greatly improve the utilization rate of local corn straw, while also making use of local attapulgite and nitrogen-rich industrial products, and can even treat local chromium pollution.
[0040] The photocatalyst was used to prepare ATP / BC / gC 3 N 4 Composite photocatalytic materials can be effectively utilized, solving the bottleneck problems of traditional adsorbents' small adsorption capacity for Cr(VI), secondary pollution, and unstable reduction efficiency, providing technical support for the high-value utilization of local advantageous resources.
[0041] Through biochar and gC 3 N 4 The coupling effect is expected to broaden the gC 3 N 4 The visible light response range is improved, the separation efficiency of photogenerated carriers is improved, the local outstanding environmental protection problems are solved, and the technology is provided for the practical application of photocatalytic technology. After preliminary experiments, the ATP / BC / gC 3 N 4 Composite photocatalytic materials can even use integrated light sources in the fields to moderately purify contaminated soil.
[0042] Systematic research on scientific issues such as the adsorption mechanism during the reaction, the separation of electron-hole pairs during the photocatalytic reduction reaction, charge transfer, and the interaction between the catalyst surface and Cr(VI) provides a basis for future exploration of the basic photocatalytic reduction reaction mechanism.
[0043] Preparation of ATP / BC / gC by calcination in one pot 3 N 4 Composite photocatalytic material, using attapulgite to adsorb cracked oil to improve its single hydroxyl functional group on the surface, increasing the adsorption reaction active sites with Cr(VI). 3 N 4 The binding of gC 3 N 4 The visible light catalytic activity of the project is good. Therefore, the implementation of the project has a good application prospect. The complex after calcination has good stability and has the opportunity to play a role in the field for a long time. It can also be compounded into fertilizers for use.
[0044] It provides a feasible idea for the development and utilization of local advantageous resources and a feasible solution for the treatment of local chromium-contaminated soil. The implementation of the project has certain social value.
[0045] The basic principle, main features and advantages of the present invention are shown and described above. Those skilled in the art should understand that the present invention is not limited to the above embodiments, and the above embodiments and descriptions are only for explaining the principles of the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, and these changes and improvements all fall within the scope of the protection required.
Claims
1. Attapulgite biochar graphite phase carbon nitride composite photocatalyst, characterized in that: Its components are attapulgite biochar graphite phase carbon nitride.
2. A method for preparing a attapulgite biochar graphite phase carbon nitride composite photocatalyst, characterized in that: The attapulgite, corn straw and dicyandiamide were mixed and the mixture was pyrolyzed at high temperature to construct a attapulgite / biochar / graphite phase carbon nitride composite photocatalytic system.
3. The method for preparing the attapulgite biochar graphite phase carbon nitride composite photocatalyst according to claim 2, characterized in that: The surface structure of attapulgite was modified by organic functional groups produced in the biomass pyrolysis process to prepare attapulgite / biochar composite materials with excellent adsorption performance for Cr(VI). The composite materials were used as catalyst carriers. The large specific surface area of the carrier was utilized to increase the dispersion of g-C3N4 on the carrier surface, increase the photocatalytic active sites, and broaden the light response range of g-C3N4, so as to achieve the adsorption of Cr(VI) and in situ visible light photocatalytic reduction of Cr(VI) under visible light conditions.
4. The method for preparing the attapulgite biochar graphite phase carbon nitride composite photocatalyst according to claim 2, characterized in that: A one-pot method is used to prepare the mixture during high-temperature pyrolysis; biochar and attapulgite have high specific surface areas, which can show enhanced adsorption performance for pollutants and increase the contact between the composite material and pollutants; in addition, the large specific surface area of the carrier can increase the surface dispersibility of g-C3N4, prevent its agglomeration, and provide more active sites for photocatalytic reactions; thirdly, the dispersed photocatalyst can improve the separation efficiency of photogenerated carriers and increase the photocatalytic activity; attapulgite is used to adsorb cracking oil to improve its single surface hydroxyl functional group and increase the active sites for the adsorption reaction with Cr(VI).
5. The method for preparing the attapulgite biochar graphite phase carbon nitride composite photocatalyst according to claim 2, characterized in that: The attapulgite is purified attapulgite; its preparation method comprises the following steps: using attapulgite raw soil and a sodium hexametaphosphate container, stirring a microsuspension, and then using heating and ultrasonic stirring to make an ultra-dispersed attapulgite particle suspension, and then obtaining purified attapulgite after static and stratification.
6. The method for preparing the attapulgite biochar graphite phase carbon nitride composite photocatalyst according to claim 2, characterized in that: Attapulgite / biochar composites were prepared by physical blending and high-temperature pyrolysis of attapulgite and crushed corn straw. While preparing corn straw-based biochar by high-temperature pyrolysis, the attapulgite was thermally activated to increase the specific surface area of the attapulgite and adsorb pyrolysis oil. A large number of organic functional groups were formed on the surface of the attapulgite, which synergistically increased the adsorption and complexing capacity of Cr (VI) with the excellent physical and chemical properties of biochar and could repair damaged soil.
7. The method for preparing the attapulgite biochar graphite phase carbon nitride composite photocatalyst according to claim 2, characterized in that: The pyrolysis temperature of the mixture is 300-700°C.
8. The method for preparing the attapulgite biochar graphite phase carbon nitride composite photocatalyst according to claim 2, characterized in that: After attapulgite, corn straw and dicyandiamide are mixed, a uniform suspension is obtained by ultrasonic stirring, and then attapulgite biochar graphite phase carbon nitride composite photocatalyst is obtained by suction filtration and drying.
9. Use of attapulgite biochar graphite phase carbon nitride composite photocatalyst as a substance for adsorbing heavy metals.
10. Use of the attapulgite biochar graphite phase carbon nitride composite photocatalyst as a substance for in-situ photocatalysis and reduction of composite materials; or use of the attapulgite biochar graphite phase carbon nitride composite photocatalyst as a substance for in-situ photocatalysis and reduction of composite materials or simultaneously as a substance for adsorbing heavy metals.
Citation Information
Cited By
Aquaculture water environment restoration agent and preparation method thereof
CN120483388A